2022
DOI: 10.1186/s12917-022-03241-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of endoscopic retrograde cholangiopancreatography and therapeutic value of endoscopic sphincterotomy in dogs with suspected hepatobiliary disorders

Abstract: Background Conventional diagnostic methods have some limitations in diagnosing specific causes of canine hepatobiliary disorders. In the evaluation of the hepatobiliary system in dogs, ultrasonography (US) is the first imaging method of choice. Nonetheless, endoscopic retrograde cholangiopancreatography (ERCP) has also been proven to be a practicable technique for evaluating canine hepatobiliary (endoscopic retrograde cholangiography, ERC) and pancreatic duct (endoscopic retrograde pancreatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a study of 45 dogs with cholangitis confirmed by histopathology, ultrasonography showed a distended GB in 24 dogs (53.3%) [1]. In a retrospective study, ultrasonography revealed distended GB in three of seven dogs with various types of cholangitis; one out of those three dogs had concurrent biliary stasis [17].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a study of 45 dogs with cholangitis confirmed by histopathology, ultrasonography showed a distended GB in 24 dogs (53.3%) [1]. In a retrospective study, ultrasonography revealed distended GB in three of seven dogs with various types of cholangitis; one out of those three dogs had concurrent biliary stasis [17].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that ERCP is technically demanding in live dogs, with a success rate between 66% and 87%. The risk of complications seems to be low but should be considered when planning ERCP in canine patients [16,17]. MRCP is a less invasive alternative to diagnostic ERCP and may be a beneficial imaging tool to distinguish patients that require therapeutic ERCP from those requiring abdominal surgery or medical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation